RUMAH KOST UNTUK MILENIAL - Ivan Laksana Setiadi; Mieke Choandi (Jurusan Arsitektur dan Perencanaan, 2019)
West Jakarta that has a dense millennial population. Basically, millennials live on technological developments, therefore, technology is extremely influential for the millennial generation, but as the year grows, an impending phenomenon occurs in the millennial generation, such as the increase in the price of housing. These events greatly affect the life to come. The increase in housing prices rose twice as fast than the millennial's salary increase. Therefore the millennial generation is threatened by the possibility of not being able to afford a housing. The proposal for the